2020
DOI: 10.1177/1082013220944009
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of bioactive compounds content in granadilla (Passiflora ligularis) seeds after solid-state fermentation

Abstract: Fermentation improves the bioactivity of fruit by-products; therefore, this study aimed to increase the bioactive compound content in granadilla ( Passiflora ligularis) seed flour (with 50% and 70% initial moisture) through solid-state fermentation using the fungus Aspergillus niger. The extracts were obtained with distilled water, 40% acetone, 80% acetone, 40% ethanol, or 80% ethanol. The highest total phenolic (4713.3 of gallic acid equivalent/100 g of granadilla seed flour in dry basis) and total flavonoid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 32 publications
3
2
0
Order By: Relevance
“…6a, there was a significant difference between the control sample and treatments 7 and 8 (p < 0.05), observing that the solid-state fermentation process enhanced the total phenolic content in 106.7 and 176, 2% respectively. This comportment was comparable to that observed by Santos et al [88] who used SSF in dehydrated granadilla seeds using Aspergillus niger, finding that the total phenolic content increased 236.5% compared to the unfermented samples and using 80% acetone as extraction solvent. In addition, Feitosa et al [89] performed SSF on moringa leaves using A. niger.…”
Section: Analysis Of the Control Sample With Respect To The Treatment...supporting
confidence: 87%
“…6a, there was a significant difference between the control sample and treatments 7 and 8 (p < 0.05), observing that the solid-state fermentation process enhanced the total phenolic content in 106.7 and 176, 2% respectively. This comportment was comparable to that observed by Santos et al [88] who used SSF in dehydrated granadilla seeds using Aspergillus niger, finding that the total phenolic content increased 236.5% compared to the unfermented samples and using 80% acetone as extraction solvent. In addition, Feitosa et al [89] performed SSF on moringa leaves using A. niger.…”
Section: Analysis Of the Control Sample With Respect To The Treatment...supporting
confidence: 87%
“…The findings of the study are in agreement with earlier research on fermented seeds, which showed that fermentation increased the phenolic content of the seeds (Osete-Alcaraz et al, 2019;Inada et al, 2020Santos et al, 2021. Phenolic compounds are typically bound to sugar, reducing their bioavailability to the body.…”
Section: Discussionsupporting
confidence: 92%
“…Concerning the occurrence of galloyl lipophenols in plant-based foods and coproducts, and more specifically, ethyl gallate, and propyl gallate, higher concentrations have been reported in granadilla (Passiflora ligularis) and tamarind (Tamarindus indica) seeds of fermented flour using Aspergillus niger. , More closely related to the matrices studied in the present work, other authors have observed valuable contents of ethyl gallate in grape seed, skin, stem, and whole pomace extracts (345.30, 86.30, 130.30, and 259.20 μg/g dw, respectively), because of the alcoholic fermentation, to which the grape pomace was subjected before analysis . These concentrations were above those recorded in the present study, possibly due to ethyl gallate being expressed as p -hydroxybenzoic acid equivalents and not being quantified with the appropriate standard.…”
Section: Resultssupporting
confidence: 74%